Bispecific antibodies for the treatment of relapsed/refractory multiple myeloma: updates and future perspectives - Parrondo, Ricardo D.; Ailawadhi, Sikander; Cerchione, Claudio (Frontiers in Oncology, 2024)
Patients with relapsed/refractory multiple myeloma (RRMM) that are refractory to the five most active anti-MM drugs, so-called penta-refractory MM, have historically had dismal outcomes with subsequent therapies. Progressive immune dysfunction, particularly of the T-cell repertoire, is implicated in the development of disease progression and refractory disease. However, the advent of novel immunotherapies such as bispecific antibodies are rapidly changing the treatment landscape and improving the survival outcomes of patients with RRMM. Bispecific antibodies are antibodies that are engineered to simultaneously engage cytotoxic immune effector cells (T cells or NK cells) and malignant plasma cells via binding to immune effector cell antigens and extracellular plasma cell antigens leading to immune effector cell activation and malignant plasma cell destruction. Currently, bispecific antibodies that bind CD3 on T cells and plasma cell epitopes such as B-cell maturation antigen (BCMA), G-protein coupled receptor family C group 5 member D (GPRC5d), and Fc receptor homologue 5 (FcRH5) are the most advanced in clinical development and are showing unprecedented response rates in patients with RRMM, including patients with penta-refractory disease. In this review article, we explore the available clinical data of bispecific antibodies in RRMM and summarize the efficacy, safety, toxicity, clinical outcomes, mechanisms of resistance, and future directions of these therapies in patients with RRMM.